2009
DOI: 10.1159/000242252
|View full text |Cite
|
Sign up to set email alerts
|

Economic Impact of Alternative Adjuvant Chemotherapy Regimens for Stage III Colon Cancer

Abstract: Background: Adjuvant treatment of stage III colon cancer represents a significant economic burden for the German health care system. The available chemotherapy regimens have significantly different medical and economic profiles. Methods: A modeling study based on published clinical trials was performed to assess costs of 5 different regimens (Mayo Clinic, LV5FU2, FOLFOX-4, Xelox, Capecitabine) from the perspective of the statutory sickness funds. Costs were calculated based on the assumption that patients were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 10 publications
(14 reference statements)
0
3
0
Order By: Relevance
“…Because it can be debated which year’s data are optimal for calibration, we tested the model with the original United States – based calibration and found that compared with the year 2000 German-based calibration, the cost-effectiveness analyses results did not differ with respect to ranking of strategies or dominance between strategies, and that while incremental cost-effectiveness ratios changed some, the differences were not substantial enough to affect interpretation or conclusions. Cost inputs were derived from a literature review 25 26 27 , the doctor’s fee scale and procedure reimbursement (Einheitlicher Bewertungsmaßstab: EBM) catalogue 2011 for office-based physicians with an EBM point value of € 0.035 28 , German Diagnostic Related Group (DRG) codes for hospitalizations 29 , and expert consultations ( Appendix ).…”
Section: Methodsmentioning
confidence: 99%
“…Because it can be debated which year’s data are optimal for calibration, we tested the model with the original United States – based calibration and found that compared with the year 2000 German-based calibration, the cost-effectiveness analyses results did not differ with respect to ranking of strategies or dominance between strategies, and that while incremental cost-effectiveness ratios changed some, the differences were not substantial enough to affect interpretation or conclusions. Cost inputs were derived from a literature review 25 26 27 , the doctor’s fee scale and procedure reimbursement (Einheitlicher Bewertungsmaßstab: EBM) catalogue 2011 for office-based physicians with an EBM point value of € 0.035 28 , German Diagnostic Related Group (DRG) codes for hospitalizations 29 , and expert consultations ( Appendix ).…”
Section: Methodsmentioning
confidence: 99%
“…Aballea et al concluded that the incremental cost-effectiveness ratio of FOLFOX4 compared favourably with other funded interventions in oncology in the USA and was likely to be cost effective compared with 5-FU/LV in the adjuvant treatment of stage III CC [45]. For Goerner et al, FOLFOX4 was the most effective adjuvant treatment for stage III CC, representing the current standard in Germany, but was also the most expensive treatment [46]. Conversely, XELOX was found to be a slightly less costly alternative to FOLFOX4 when oral treatment is preferred [46].…”
Section: Cost-benefi T Of Adjuvant Therapymentioning
confidence: 99%
“…For Goerner et al, FOLFOX4 was the most effective adjuvant treatment for stage III CC, representing the current standard in Germany, but was also the most expensive treatment [46]. Conversely, XELOX was found to be a slightly less costly alternative to FOLFOX4 when oral treatment is preferred [46]. The reduced need for drug administration visits and central venous access with XELOX reduces patient travel and productivity losses, providing patients the freedom to live as normal a life as possible.…”
Section: Cost-benefi T Of Adjuvant Therapymentioning
confidence: 99%